Meningeal TB in a 39-Year-Old Male Presenting with Headache - Jason Selinger; Thar El Baage (Case Reports in Infectious Diseases)
Meningeal tuberculosis is rare in the developed world, with only 92 cases of meningeal TB reported in the United States in 2014 according to the CDC (CDC, 2015). We describe the case of a 39-year-old male with a history of alcohol abuse, whose cerebral spinal fluid acid fast smears confirmed TB only weeks after his death. His only initial presenting symptom was headache, and his condition declined rapidly during his hospitalization.